Gene expression profiling of E2F-1-induced apoptosis - Jamshidi-Parsian, A.; Dong, Y.; Zheng, X.; Sam Zhou, H.; Zacharias, W.; McMasters, K.M.
It has been shown that adenovirus-mediated overexpression of E2F-1 can efficiently induce apoptosis in cancer cells with little effect on normal cells. However, the mechanisms by which E2F-1 induces apoptosis remains poorly understood. The goal of this study was to evaluate changes in gene expression in response to E2F-1 in order to help elucidate the mechanisms by which E2F-1 causes apoptosis. Therefore, we used a quantitative microarray assay to identify the genes regulated by E2F-1 in melanoma cells. By gene expression profiling, we first screened a proprietary list of about 12,000 genes. Overexpression of E2F-1 in melanoma cells resulted in two-fold or greater alteration in the level of expression of 452 genes compared to vehicle-treated control cells. Most of the affected genes were not known to be responsive to E2F-1 prior to this study. E2F-1 adenoviral infection of these cells was found to affect the expression of a diverse range of genes, including oncogenes, transcription factors and genes involved in signal transduction, cell cycle regulation, cell proliferation and apoptosis, as well as other genes with unknown function. Changes in expression of 17 of these genes were confirmed by quantitative real-time polymerase chain reaction (PCR). This is first application of the microarray technique in the study of the global profile of genes regulated by E2F-1 in melanoma cells. This study leads to an increased understanding of the biochemical pathways involved in E2F-1-induced apoptosis and possibly to the identification of new therapeutic targets.
Keywords: ADENOVIRUS; CELL CYCLE; ASK-1; MICROARRAY; MELANOMA; GENE THERAPY